MeJA-induced hairy roots in Plumbago auriculata L. by RNA-seq profiling and key synthase provided new insights into the sustainable production of plumbagin and saponins - Li, Yirui; Zhao, Zi-an; Hu, Ju; Lei, Ting; Chen, Qibing; Li, Jiani; Yang, Lijuan; Hu, Di; Gao, Suping (Frontiers in Plant Science, 2024)
The synthesized secondary metabolites in plants naturally are considered an important source of drugs, food additives, etc. Among them, research on natural plant medicinal components and their synthesis mechanisms has always been of high concern. We identified a novel medicinal floral crop, Plumbago auriculata L, that can be treated with MeJA for the rapid or sustainable production of natural bio-actives from hairy roots. In the study, we globally analyzed the changes in the accumulation of plumbagin and others in the hairy roots of PAHR 15834 in Plumbago auriculata L. based on 100 μmol/L MeJA treatment by RNA-Seq profiling, and we found that there was the significant in the accumulation of plumbagin and saponin before 24h. To explain the principle of co-accumulation, it showed that MeJA induced JA signaling and the shikimic acid pathway, and MVA pathway was activated downstream subsequently by the Mfuzz and weighted gene co-expression analysis further. Under the shared metabolic pathway, the high expression of PAL3 and HMGR promoted the activity of the "gateway enzymes"-PAL and HMGR, which respectively induced the high expression of key reaction enzyme genes, included in CHSs, IPPs, and FPSs, that lead to the synthesis of plumbagin and saponin. We speculated that large amounts of ketones and/or aldehydes were formed under the action of these characteristic enzymes, ultimately achieving their co-accumulation through polyketone and high-level sugar and amino acid metabolism. The study results provided a theoretical basis for carrying out the factory refining and biosynthesis of plumbagin and saponins, and provided new ideas for fully exploiting multifunctional agricultural crops and plants, and developing new agricultural by-products.